Eco granja Wayúu (proyecto Polowii) (2021)
The project was born by determining the intervention context, where the department of La Guajira in northern Colombia was identified, from there the architectural problem is recognized and how a project on a zonal scale can help mitigate a social problem in the region; For this, the municipality of Uribía to the north of La Guajira is chosen, due to its weather conditions and its social problems to be addressed, where poverty and the food crisis that mainly plagues the Wayúu indigenous community is identified, said the above, it is decided to project an eco farm Wayúu focused on the production and collection of food. The investigation of the place begins with the analysis of why was Uribía chosen as the place of intervention? Subsequently, when investigating bioclimatic factors of the area where the desert ecosystem and the deficit of rainfall in this municipality are identified and the complete relationship of this municipality with the Wayúu tribes.